2021
DOI: 10.1096/fj.202101279r
|View full text |Cite
|
Sign up to set email alerts
|

BCAS2 is involved in alternative splicing and mouse oocyte development

Abstract: Alternative splicing (AS) is an important mechanism to regulate organogenesis and fertility. Breast carcinoma amplified sequence 2 (BCAS2) is one of the core components of the PRP19 complex, a multiple function complex including splicing, and it is involved in the initiation of meiosis through regulating AS in male mice. However, the role of BCAS2 in mouse oogenesis remains largely unknown. In this study, we found that BCAS2 was highly expressed in the oocytes of primordial follicles. Vasa‐Cre‐mediated deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(156 reference statements)
0
8
0
Order By: Relevance
“…To acquire a sufficient number of oocytes, 7.5 IU of pregnant mare’s serum gonadotropin (PMSG, Ningbo Pharmacy Factory, China) was injected into a 6-week-old female, and the cumulus-oocyte-complexes (COCs) were obtained after 44–46 h by puncturing ovarian antral follicles as described in a previous study [ 50 ]. Finally, GV-stage COCs were cultured in an M16 medium (Sigma Chemical Co., St. Louis, MO, USA) in a humidified atmosphere of 5% CO 2 at 37.5 °C for 5 and 12 h to count GVBD- and MII-stage oocytes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To acquire a sufficient number of oocytes, 7.5 IU of pregnant mare’s serum gonadotropin (PMSG, Ningbo Pharmacy Factory, China) was injected into a 6-week-old female, and the cumulus-oocyte-complexes (COCs) were obtained after 44–46 h by puncturing ovarian antral follicles as described in a previous study [ 50 ]. Finally, GV-stage COCs were cultured in an M16 medium (Sigma Chemical Co., St. Louis, MO, USA) in a humidified atmosphere of 5% CO 2 at 37.5 °C for 5 and 12 h to count GVBD- and MII-stage oocytes, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous reports, BCAS2 is involved in mRNA splicing through the PRP19 complex [ 14 , 26 ]. To further explore how BCAS2 participates in RNA processing in granulosa cells, we performed Co-IP and revealed that BCAS2 interacts with PRP19 complex core proteins (Fig.…”
Section: Bcas2 Regulated the Cellular Senescence Of Functional Genesmentioning
confidence: 99%
“…Specific disruption of Bcas2 in male germ cells affected mouse spermatogenesis and male fertility by regulating AS, which decreases the full-length formation of deleted azoospermia-like ( Dazl ) [ 25 ]. Vasa-Cre mediated deletion of Bcas2 caused poor oocyte quality, abnormal oogenesis, and follicular development, possibly by regulating the AS of functional genes through the PRP19 complex [ 26 ]. Maternal depletion of Bcas2 by Zp3-Cre mice destroyed the genomic integrity of early embryos and resulted in female infertility [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that loss of BCAS2 in oocytes leads to poor oocyte quality, abnormal oogenesis, and disrupted follicular development. Further studies have found that the destruction of BCAS2 leads to the degradation of the PRP19 core protein in mouse oocytes, which affects AS 21 . BCAS2 is essential for female mouse fertility as it maintains genome integrity in early embryos via modulation of DNA repair modulation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have found that the destruction of BCAS2 leads to the degradation of the PRP19 core protein in mouse oocytes, which affects AS. 21 BCAS2 is essential for female mouse fertility as it maintains genome integrity in early embryos via modulation of DNA repair modulation. 22 However, the role of BCAS2 in oocyte meiosis has not been reported.…”
Section: Introductionmentioning
confidence: 99%